Clinical significance of circulating tumor cells in predicating the outcomes of patients with colorectal cancer - Chen, Kehe; Chen, Zhenxiang; Ou, Mei; Wang, Junping; Huang, Xiao; Wu, Yingying; Zhong, Wenhe; Yang, Jiao; Huang, Jinging; Huang, Min; Pan, Deng (Clinics, 2022)
Background: Relapse and metastasis of patients with Colorectal Cancer (CRC) is the major obstacle to the long-term life of patients. Its mechanisms remain defined. Methods: A total of 48 CRC patients were enrolled and 68 samples were obtained from the peripheral blood of patients before or after treatments in this study. Twenty non-cancer patients were also detected as a negative control. Circulating Tumor Cells (CTCs), including Epithelial CTCs (eCTCs), Mesenchymal (MCTCs), and epithelial/mesenchymal mixed phenotypes (mixed CTCs), were identified by CanPatrolTM CTC enrichment and RNA in situ hybridization. The relationship between CTCs number and Progression-Free Survival (PFS) or Overall Survival (OS) was evaluated. Results: Thirty-four of 48 patients (70.8%) were found to have positive CTCs. Total CTCs and MCTCs in the post-treatment had a significant correlation PFS and OS. When total CTCs or MCTCs in 5 mL blood of patients were more than 6 CTCs or 5 MCTCs, PFS of the patients was significantly shorter (p < 0.05) than that in patients with less than 6 CTCs or 5 MCTCs. The patients with > 5 CTCs count changes were found to exhibit poor PFS and OS rates (p < 0.05). Conclusion: Total CTCs and MCTCs number detection in patients with colorectal cancer was very useful biomarker for predicting the prognosis of patients. Higher CTCs or MCTCs had poorer PFS and OS rates.